PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS SAINTIFIK MATERI SISTEM GERAK PADA MANUSIA KELAS VIII SMP NEGERI 1 ARAMO - Buulolo, Samitina (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The aim of this research is to find out and produce scientific-based learning materials on human movement systems in class VIII SMP that are valid, practical and effective. The method in this research uses research methods in the form of development or Research and Development (R&D). Based on the results of the module development, the scientific-based development of the human movement system module was declared valid, practical and effective for improving student learning outcomes. It is said to be valid because this teaching material has been validated by three validators so that it can be used by teachers and students, and during the practicality test on teachers and students this teaching material is easy to use and very effective for motivating students in learning activities. Based on the research results and conclusions that have been described previously, there are several suggestions in this research which are as follows: 1) Students can use this scientific-based science learning module in science learning. 2) Science subject teachers can use this scientific-based learning module teaching materials to support learning activities, especially in class VIII of SMP Negeri 1 Aramo. 3) For SMP Negeri 1 Aramo schools, they can use this scientific-based learning module to increase their knowledge and understanding in making teaching materials. 4) For future researchers, this research can be a source of information in developing scientific-based science modules that can now be used in other subjects. 5) For researchers, these researchers can increase knowledge and expand the preparation of scientific work regarding movement sites in humans. 6) For students, this research can be a source of information for the same researchers with a wider scope.